Large eddy simulation of ABL flow around a parabolic concave roof model - Zulfadli Bin Abdul Latiff (2016)
Numerical simulation by means of Large Eddy Simulation (LES) was carried out to study the effects of an Atmospheric Boundary Layer (ABL) flow around a parabolic concave roof model. The effects of inflow wind velocity and sag depth of the roof on time averaged drag coefficient, C_D , and pressure coefficient, C_P , was investigated. Reynolds number was kept above (2-3)*10^4 to allow for scalability. It was found that C_D increases as flow velocity increases, opposing the general trend for flow around a bluff body that C_D will decrease when Reynolds number increases. This is possibly due to the flow in the concaved region of the roof. C_P decreases on both the windward wall and leeward wall as flow velocity increases. As sag depth increases, C_D increases and the magnitude of C_P increases on both the windward wall and leeward wall.